2015
DOI: 10.1111/jpi.12222
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces oxidative stress and improves vascular function in pulmonary hypertensive newborn sheep

Abstract: Pulmonary hypertension of the newborn (PHN) constitutes a critical condition with severe cardiovascular and neurological consequences. One of its main causes is hypoxia during gestation, and thus, it is a public health concern in populations living above 2500 m. Although some mechanisms are recognized, the pathophysiological facts that lead to PHN are not fully understood, which explains the lack of an effective treatment. Oxidative stress is one of the proposed mechanisms inducing pulmonary vascular dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 76 publications
(104 reference statements)
8
92
0
11
Order By: Relevance
“…Consistent with findings in previous studies [24,26], we found that chronic hypoxia induced a significant elevated level of lipid peroxidation in the lungs, which was mitigated by the melatonin treatment. It has been shown that hypoxia increased the levels of lipid peroxidation in pulmonary endothelial cells and also the plasma glutathione disulfide in the animal [27,28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with findings in previous studies [24,26], we found that chronic hypoxia induced a significant elevated level of lipid peroxidation in the lungs, which was mitigated by the melatonin treatment. It has been shown that hypoxia increased the levels of lipid peroxidation in pulmonary endothelial cells and also the plasma glutathione disulfide in the animal [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, melatonin could induce endothelium-dependent vasorelaxation with an increase in the NO production mediated by elevated NOS activity [22,23]. Recent studies have shown that melatonin treatment could elevate the NO availability in the lungs of newborn sheep at high altitude [24] and also alleviate the severe pulmonary hypertension induced by monocrotaline [25] or intermittent hypoxia [26] in rats. However, it is unclear whether the melatonin treatment might ameliorate the pulmonary hypertension induced by chronic hypoxia, which is clinical relevance to the pathophysiological cascade in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also showed that melatonin has emerged as a promising resource for improving neurological recovery from stroke and ischemic brain damage in adults . Torres et al showed that melatonin reduces oxidative stress and improves vascular vasodilator function of small pulmonary arteries in pulmonary hypertensive newborn sheep . The mechanisms by which melatonin prevents placental malperfusion remains uncertain, but research has focused on melatonin's antioxidative and anti‐inflammatory effects and its immune modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Novel treatments have been proposed to decrease the oxidative stress and diminish pulmonary hypertension and cardiovascular remodeling. Recently, we have shown that melatonin increases the enzymatic antioxidants mechanisms and improves pulmonary endothelial function associated with a slight increase of the luminal radius of pulmonary arteries [70]. Interestingly, the same treatment also improved vascular function and decreased oxidative stress in the neonatal brain [95].…”
Section: Perinatal Cardiovascular Responses and Treatmentmentioning
confidence: 96%
“…The pulmonary hypertension is a condition with an elevated pulmonary vascular PVR, as a result of an initial vasoconstriction followed by a progressive vascular remodeling [67,69,70]. Both, vascular vasoconstriction and vascular remodeling end up in a significant reduction of the lumen of the intrapulmonary arteries increasing the PVR [65,67,71].…”
Section: Perinatal Cardiovascular Responses and Treatmentmentioning
confidence: 99%